Novel treatments for rare rheumatologic disorders: analysis of the impact of 30 years of the US orphan drug act - Lutz, Thomas; Lampert, Anette; Hoffmann, Georg F.; Ries, Markus (Orphanet journal of rare diseases, 2016)
Background - Rare rheumatologic diseases are a heterogeneous group of conditions associated with high morbidity. As a whole group, rare rheumatologic diseases afflict millions of people demanding for effective therapies. Therefore, we analyzed the impact of the US Orphan Drug Act on the development of anti-rheumatic orphan drugs. - - Methods - Analysis of the FDA database for orphan drug designations. - - Results - In the last three decades, out of 77 orphan drug designations, 14 orphan drug approvals were granted by the FDA for the treatment of rare rheumatologic disorders, i.e. juvenile idiopathic arthritis (N = 5), cryopyrin-associated periodic syndromes (N = 3), uveitis (N = 3), familial Mediterranean fever (N = 1), anti-neutrophil cytoplasmic antibody-associated vasculitis (N = 1), and xerostomia and keratoconjunctivitis sicca in Sjögren’s syndrome (N = 1). Mean time (standard deviation) from designation to approval was 3.9 (2.81) [range 1 … 12] years. Number of FDA-approved small molecules (N = 6, 43 %) and biologics (N = 8, 57 %) was comparable. Almost every fifth (19 %) orphan drug designation was withdrawn. Despite the rarity of conditions, 13/14 pivotal studies were randomized controlled trials. - - Conclusions - Orphan drug development is challenging: thirty years of US orphan drug act supported the development and FDA approval of 14 orphan drug programs with anti-rheumatic compounds for six rheumatologic diseases.
Gesehen am 08.05.2019